2013
DOI: 10.1007/s00234-013-1302-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ipsilateral parenchymal hemorrhage following treatment of intracranial aneurysms with flow diverter

Abstract: From the literature review, DIPH appears to be more frequent than delayed aneurysm rupture and may be a cause of increasing concern for the use of flow diverters. However, the mechanisms of DIPH are not completely understood. Surgical evacuation of the hematoma seems to be feasible with acceptable safety and good clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…Remarkably, no delayed aneurysm rupture or intracranial parenchymal hemorrhage was reported. 20,21 The present results also highlight the high quality of aneurysm occlusion obtained with this technique, confirming the data from 6-month follow-up in the WEBCAST and from an already published retrospective European series. 14,15,17 initial experience with WEB aneurysm treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Remarkably, no delayed aneurysm rupture or intracranial parenchymal hemorrhage was reported. 20,21 The present results also highlight the high quality of aneurysm occlusion obtained with this technique, confirming the data from 6-month follow-up in the WEBCAST and from an already published retrospective European series. 14,15,17 initial experience with WEB aneurysm treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, 1 small study of 4 patients with post-flow-diverter-therapy IPH and imaging in the immediate postoperative period before the IPH found no cases of ischemic lesions preceding the development of IPH. 23 The exact cause behind the significantly increased incidence following treatment of ruptured aneurysms as noted in our study is not clear. It is possible that the increased acute-phase reactant environment could facilitate platelet activation and result in subsequent embolic and thereby hemorrhagic events.…”
Section: Discussionmentioning
confidence: 60%
“…Last, we do not have any consistent data regarding how these hemorrhages were managed. A recent study by Tomas et al 23 demonstrated that surgical evacuation of IPHs following flowdiverter treatment resulted in favorable clinical outcome on follow-up. These procedures were safe and effective in all 4 cases in the Tomas et al study, despite the use of dual antiplatelet therapy as all patients had platelet transfusion immediately before the surgical procedure.…”
Section: Limitationsmentioning
confidence: 99%
“…Most described parenchymal hemorrhages following flow diversion are supratentorial and result in a severe clinical deficit. 3,5,17 Most interesting, in this case, we had the opportunity of obtaining MR imaging before the brain stem hemorrhage, but it did not show a focus of diffusion restriction or susceptibility effect as a clue to the cause of the hemorrhage. The only caveat was that DWI can fail to detect a small brain stem infarct when performed early after the stroke (day 2 postoperative in this case).…”
Section: Discussionmentioning
confidence: 84%
“…[1][2][3][4][5] Speculation remains regarding the etiology of both forms of hemorrhage, with an overall hemorrhage risk of 7% in reported series. 6 Delayed parenchymal hemorrhages typically occur on the side of the treated aneurysm and at an incidence in excess of that expected due to dual antiplatelet medication alone and from that reported in prior non-flow-diverting-stent literature.…”
mentioning
confidence: 99%